2018
DOI: 10.1186/s12909-018-1210-6
|View full text |Cite
|
Sign up to set email alerts
|

Tools and resources for neuroanatomy education: a systematic review

Abstract: BackgroundThe aim of this review was to identify studies exploring neuroanatomy teaching tools and their impact in learning, as a basis towards the implementation of a neuroanatomy program in the context of a curricular reform in medical education.MethodsComputer-assisted searches were conducted through March 2017 in the PubMed, Web of Science, Medline, Current Contents Connect, KCI and Scielo Citation Index databases. Four sets of keywords were used, combining “neuroanatomy” with “education”, “teaching”, “lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 46 publications
(41 reference statements)
0
44
0
12
Order By: Relevance
“…The development and use of alternative methods for teaching neuroanatomy, therefore, are expected to increase in the next few years (Shaffer, 2004;Winkelmann, 2007). Alternative teaching methods in the form of technological innovations will appeal to the modern, digital student (Pani et al, 2013;Drapkin et al, 2015;Allen et al, 2016;Arantes et al, 2018). Various reports have shown that students have a preference for new teaching methods because they are considered to be interactive, engaging, and widely available (Shen et al, 2008;Huang et al, 2010;Drapkin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The development and use of alternative methods for teaching neuroanatomy, therefore, are expected to increase in the next few years (Shaffer, 2004;Winkelmann, 2007). Alternative teaching methods in the form of technological innovations will appeal to the modern, digital student (Pani et al, 2013;Drapkin et al, 2015;Allen et al, 2016;Arantes et al, 2018). Various reports have shown that students have a preference for new teaching methods because they are considered to be interactive, engaging, and widely available (Shen et al, 2008;Huang et al, 2010;Drapkin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the field of anatomy, some studies revealed that the students who used CAL or web‐based resources more frequently obtained better performances in examinations when compared with students who had never accessed these resources (Hallgren et al, 2002; McNulty et al, 2009; Kish et al, 2013). Furthermore, in the neuroanatomy domain, Arantes et al (2018) found that using CAL contributes to improve academic performance and that learners also express positive attitudes toward this pedagogical approach. Pani and colleagues suggest that computer‐based learning environments facilitate the teaching and learning process in neuroanatomy, since interactive computer graphics and the computers' ability to manage information management may provide good support for self‐study in this area (Pani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, use of 3D media is well established in academic and clinical neurosurgery. 19-23 Investigators use stereoscopic imaging diversely, ranging from side-by-side figures in journals to custom virtual simulators built from scratch. 19,20,24 These endeavors into next-generation surgical simulation provide insight toward the use of virtual reality (VR) in LSB surgical training.…”
mentioning
confidence: 99%